From pharmacokinetics to precision dosing: optimizing continuous infusion regimens of ciprofol for elderly patients - Zhu, Jiaxi; He, Jing; Zhong, Bowen; Cao, Ying; Zhang, Xingan; Xu, Bo (Frontiers in Pharmacology, 2026)
ObjectiveTo develop and validate a population pharmacokinetic/pharmacodynamic (PK/PD) model for ciprofol in elderly surgical patients, delineating its pharmacokinetic profile and concentration-effect relationship to inform precision dosing.MethodsTwenty patients (aged ≥65 years) undergoing elective surgery were enrolled. We performed population PK/PD analysis using nonlinear mixed-effects modeling on 386 arterial blood samples and synchronized Bispectral Index (BIS) data. A linear three-compartment model and a sigmoid Emax model described the PK and PD (BIS), respectively. Covariates (age, weight, gender, and laboratory parameters) were tested via stepwise selection. Model performance was evaluated using goodness-of-fit plots, bootstrap (n = 1,000), and prediction-corrected visual predictive checks. Dosing regimens were optimized via Monte Carlo simulation.ResultsA three-compartment model best described the PK. The center volume (V1) was generally approximated at 2.95 L, but the peripheral volumes (V2 and V3) were 45.15 L and 76.79 L, respectively. The clearance (CL) was assessed at 1.01 L min-1. Body weight and age significantly influenced CL. PD analysis showed rapid effect-site equilibration (Ke0: 1.09 min-1), with an EC50 of 233.91 ng mL-1 and a Hill coefficient of 3.00. No covariates significantly affected PD parameters. The model exhibited sufficient fit and strong predictive efficacy. The simulation results confirmed that administering an intravenous loading dose of 0.4 mg kg-1 over 1 min, followed by an initial continuous infusion at a rate of 0.6 mg kg-1·h-1 for 2 h, could stably maintain the patients’ BIS values within the target range of 40–60.ConclusionA population PK/PD model for ciprofol in elderly patients was successfully established and validated. The model supports optimized, individualized dosing to achieve target anesthesia depth in this population.